Negative thermal expansion of fullerite C60 at liquid helium temperatures - Aleksandrovskii, A. N.; Esel`son, V. B.; Manzhelii, V. G. Manzhelii,B.G.; Soldatov, A. V.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The thermal expansion of fullerite C60 has been measured in the temperature range 2-9 K. A compacted fullerite sample with a diameter of about 6 mm and height of 2.4 mm was used. It was found that at temperatures below 3.4 K the linear thermal expansion coefficient becomes negative. At temperatures above 5 K our results are in good agreement with the available literature data. A qualitative explanation of the results is proposed.